Improving yield by breaking the seed furrow and covering the soil after sowing in strip-tillage mode - Xinliang Zhao; Wei Zhang (Plant, Soil and Environment, 2025)
Based on strip-tillage technology, this study explores the optimal seedbed environment for maize growth through a three-year field agronomic experiment. A comparative analysis of two planting modes, flat planting and ridge planting, was conducted, and a two-factor, three-level experimental design was implemented (furrow-breaking width: 8, 10 and 12 cm; furrow-breaking depth: 2, 3 and 4 cm), with manual soil covering without furrow breaking as the control group. Analysis of the averaged data over three years indicates that furrow-breaking treatment significantly increased maize yield under both flat and ridge planting modes, highlighting the importance of furrow breaking for maize growth. Ridge planting increased yield by an average of 7.58% compared to flat planting. The optimal yield was achieved at a furrow-breaking width of 10 cm and a depth of 4 cm, where ridge and flat planting yields were 10.37% and 10.43% higher than the average values at each level, respectively. Additionally, at the optimal yield level, the chlorophyll soil-plant analysis development (SPAD) values for ridge and flat planting were 15.36% and 17.06% higher than the average values. The emergence rates of ridge and flat planting maize were 5.43% and 4.93% higher than the average values, respectively. This not only enhanced crop stress resistance but also improved overall economic benefits.